Tingkat Stres Pada Mahasiswa Tingkat Profesi Fakultas Kedokteran Universitas Gadjah Mada - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2006)
ABSTRACT Background: Professional education program is a very important component of general medical education. The success rate in this stage of clinical really determines the quality of health service in our community at present and in the future. The transition process from academic program into clinical program and other problems that come up as the result of an individual student's interaction with the clinical education environment may cause stress to the student. This kind of stress will influence both the students' learning achievement and the quality of medical graduates. This research reveals the stress level of the students of clinical stage and the role of clinical system in causing the stress. Objectives: 1.To recognize the stress level of Gadjah Mada medical students of the clinical stage in every department and whether there were any significant stress level among them. 2. To know whether any significant stress level difference exists between the Major Group Department and the Minor Group Department. 3. To know whether any significant stress level difference exists amongst the students based on sex and other demographic data. Methods: A non-experimental research was conducted with a cross sectional study design. The research utilized closed questionnaires, each contained 4 liken scales. The questionnaires were given to all clinical stage Gadjah Mada medical students in year 2001, and then they were analyzed to find the means. These were used to know the academic, social, and personal stress levels. To be able to know whether any significant differences exist amongst the subjects' characteristic groups, we used ANOVA One Way with Tukey HSD analysis and T-test Samples Independent statistic method. Results: 1. From 2004 Gadjah Mada medical students of the clinical stage, it is found that there were not any significant differences academic stress levels among Department but there were very significant differences on social and personal stress levels. 2. There were not any significant differences between the academic, social, and personal stress levels of male and female Gadjah Mada medical students of the clinical stage. 3. There were not any significant differences between the academic stress level of the second year clinical stage students and the first year clinical stage students